Creative resources for the early childhood classroom - Herr, Judy.; Libby-Larson, Yvonne (Stamford, CT : Delmar/Thomson Learning, 2000)
Presents a collection of curriculum ideas for preschool classrooms, based upon sixty-seven themes, each with related activities; and includes a complete list of multimedia resources, and suggested children's literature.
Includes bibliographical references and index.
Adult
Keywords: Education, Preschool -- Curricula; Unit method of teaching; Preschool education -- Curricula; Teaching